Heart rate response to game load of U19 female basketball players - Vencurik, T.; Nykodym, J.; Struhar, I. (Journal of Human Sport & Exercise, 2015)
The aim of the study is to compare the intensity of game load between player positions (guards, forwards, centers) and between the 1st and the 2nd half of the basketball games in female category U19. Ten female basketball players (17.6 ± 0.9 years old) participated in this study. The beep test was used to determine the maximal heart rate (HRmax) and based on the HRmax the four intensity zones were set (< 75%, 75-84%, 85-95%, > 95% of HRmax). The heart rate (HR) and its development during the competition were monitored by telemetric device Suunto Team Pack. We did not record any statistical significance among player positions in particular intensity zones, nor in % of HRmax (86 ± 2.8 vs. 88.3 ± 2.9 vs. 87.7 ± 3.3; guards vs. forwards vs. centers). Moreover, when we compared the 1st and the 2nd half, of individual games, in particular zones and in % of HRmax (87.8 ± 3 vs. 86.8 ± 3.1) we also did not record any statistical significance. The female basketball players spent 74.3% of total time with HR greater than 85% of HRmax which indicates high physiological demands during the competition on all player positions. The results can be used for comparison with the intensity of training load and for optimizing the training process.